Associations between Life’s Crucial 9 and severity, all-cause mortality, and cardiovascular mortality in individuals with cardiovascular-kidney-metabolic syndrome: the mediating role of phenotypic age acceleration - Li, Jing; Xu, Zengxin; Lin, Jiayi; Luo, Shunxiang; Xu, Shanghua (Frontiers in Nutrition, 2025)
ObjectiveThe American Heart Association (AHA) recently introduced the concept of cardiovascular-kidney-metabolic (CKM) syndrome. This study aimed to explore the associations of Life’s Crucial 9 (LC9), the recently updated lifestyle guidelines for cardiovascular health, with the severity and mortality of CKM syndrome.MethodsFor this study, we utilized National Health and Nutrition Examination Survey (NHANES) data and conducted logistic regression analyses to evaluate the association between LC9 scores and the severity of CKM syndrome, whereas Cox regression models were employed to assess the effects of LC9 scores and mortality in patients with CKM syndrome. Subsequently, restricted cubic spline (RCS) analysis was used to investigate potential nonlinear relationships between LC9 scores and both the severity and mortality of CKM syndrome. Stratification and interaction analyses were carried out across different subgroups to validate the findings. Finally, mediation analysis was performed to investigate whether phenotypic age acceleration (PhenoAgeAccel) status mediates the association between LC9 scores and CKM syndrome severity.ResultsA total of 7,647 patients were included in our study. After adjusting for covariates, each 10% increase in the LC9 score was associated with a 37% reduction in the risk of progression to advanced CKM syndrome stages, and WQS analysis revealed that the blood glucose level was the most influential contributing factor. Moreover, Cox regression analysis revealed that higher LC9 scores were significantly linked to lower risks of all-cause mortality (HR = 0.81, 95% CI: 0.76–0.87) and cardiovascular mortality (HR = 0.74, 95% CI: 0.65–0.84) among individuals with CKM syndrome. Additionally, RCS analysis revealed a significant nonlinear association between LC9 scores and CKM syndrome severity, but no nonlinear association was found between LC9 scores and the risk of mortality. Mediation analysis confirmed that PhenoAgeAccel mediated the association between LC9 scores and CKM syndrome severity.ConclusionOur findings indicate significant negative associations of LC9 scores with CKM syndrome severity and mortality, highlighting the potential role of LC9 in guiding targeted public health strategies to prevent the progression of CKM syndrome to advanced stages and reduce mortality risk.